Grade promotions task recommendation for UiTM lecturer / Amirul Akmal Abd Karim - Abd Karim, Amirul Akmal (Faculty of Computer and Mathematical Sciences, 2016)
The Grade Promotions Task Recommendations is developed in order to help UiTM lecturer by giving the recommendation of how to get a grade promotions. Based on the interview that has been conducted to this project, it is found that lecturer are not clear on criteria that need to be fulfilled in order to obtain a grade promotions. They still need to ask a help from other lecturer about to get a grade promotion. The aim of the project is to develop the Grade Promotions Task Recommendations System for UiTM lecturers. The objectives of the project is to design the Grade Promotions Task Recommendations, to develop the system prototype in the web based system for Windows platform and to test the functionality of the system prototype. Currently the system is developed for the UiTM lecturer. The project is developed by using the fuzzy logic technique and there are about 20 rules that is used in this project. The scopes of the project covers the grade position of UiTM lecturer from DM45 to VK7. The methodology that is used in this project is prototyping methodology. Its consists only one iteration due to the limitation of time and the output will be high-fidelity which means can function. The data finding is from conducting literature review and interviews. There are 3 interviews that is conducted in order to get the data to develop this system. However, this system still need the improvement and enhancement to make its more perform better. The main suggestion for the future work of this project is to make it available in mobile platform. This is because currently the system is only available in web platform The other minor suggestion for the future work is explained well in the chapter 7 in the subtopic Recommendation of Future Works.